2011
DOI: 10.1111/j.1365-2435.2011.01929.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional ecology of saltglands in shorebirds: flexible responses to variable environmental conditions

Abstract: Summary1. Birds of marine environments have specialized glands to excrete salt, the saltglands. Located on the skull between the eyes, the size of these organs is expected to reflect their demand, which will vary with water turnover rates as a function of environmental (heat load, salinity of prey and drinking water) and organismal (energy demand, physiological state) factors. On the basis of inter-and intraspecific comparisons of saltgland mass (m sg ) in 29 species of shorebird (suborder Charadrii) from sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 59 publications
(91 reference statements)
1
39
0
Order By: Relevance
“…Obviously, diving birds exhibit a more intimate contact with water than any other birds making them more susceptible to the problems just mentioned. Other guilds such as small wading birds are more tolerant of saline conditions thanks to their salt glands (Gutiérrez et al, 2012). The pattern of a slightly greater abundance at intermediate levels of salinity (20-40 ppt) was also observed in other studies focusing on different waterbird species, and it appears to be related to prey density, especially fish and macroinvertebrates (Takekawa et al, 2006;Warnock et al, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…Obviously, diving birds exhibit a more intimate contact with water than any other birds making them more susceptible to the problems just mentioned. Other guilds such as small wading birds are more tolerant of saline conditions thanks to their salt glands (Gutiérrez et al, 2012). The pattern of a slightly greater abundance at intermediate levels of salinity (20-40 ppt) was also observed in other studies focusing on different waterbird species, and it appears to be related to prey density, especially fish and macroinvertebrates (Takekawa et al, 2006;Warnock et al, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…Both plover species possessing SO and sandpiper species lacking SO show an essentially identical pattern of substantial increase in nasal-gland mass when foraging in marine coastal habitats (Gutiérrez et al 2012). The nasal-gland mass in coastally foraging plovers and sandpipers was measured at~0.1% of body mass (Gutiérrez et al 2012), comparable to values reported for marine members of Alcidae and Laridae (Fänge et al 1958, Staaland 1967, Peaker and Linzell 1975. Among the 21 charadriiform species whose nasal glands were examined by Staaland (1967), the highest ratio of nasal gland to body mass (0.12%) was in the Red Knot, which lacks SO; this ratio is substantially higher than those reported for guillemots (genera Cepphus and Uria), the Razorbill (Alca torda), and the Dovekie (Alle alle), all marine taxa scored as having the F state of SO in the present study ( Figure 1).…”
Section: Discussionmentioning
confidence: 98%
“…The size of the nasal gland in relation to body mass shows substantial within-species variability in Charadriiformes, depending on the salinity of the environment (Gutiérrez et al 2012). Both plover species possessing SO and sandpiper species lacking SO show an essentially identical pattern of substantial increase in nasal-gland mass when foraging in marine coastal habitats (Gutiérrez et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…79 In this study, we investigated whether prey salt content and freshwater accessibility influence 80 food-discrimination behaviors using captive red knots that fed on mud snails Peringia ulvae whose 81 body fluids had either relatively low (25‰) or high (42‰) salinity. Molluscivore shorebirds face the 82 dilemma of having to conserve free water while consuming hard-shelled prey with high seawater 83 content and relatively little flesh (Gutiérrez et al 2012;Gutiérrez et al 2015). Specifically, 84 maintaining the osmotic balance is a major challenge for red knots, as they may process several 85 times their body mass in seawater each day (Visser et al 2000) with limited or no access to 86 freshwater in some of their main nonbreeding areas (Wolff and Smit 1990;van de Kam et al 2004).…”
mentioning
confidence: 99%